Impact of cavity shave margins in patients with ductal carcinoma in situ undergoing conserving breast surgery - Vanni, Gianluca; Pellicciaro, Marco; Materazzo, Marco; Marsella, Valentina; Usai, Valeria; Noce, Annalisa; Buonomo, Oreste Claudio (Frontiers in Oncology, 2024)
Aim The main challenge during breast-conserving surgery (BCS) is to obtain clear margins, especially in patients with ductal carcinoma in situ (DCIS) due to the absence of well-defined nodules. Many surgical approaches have been used in an attempt to reduce the positive margin rate. The aim of this retrospective study is to compare the cavity shave margin technique with standard surgery and the intraoperative evaluation of surgical margins. Methods This is a single-center retrospective study analyzing margin status, need for re-excision, and surgical time in a cohort of 227 patients who underwent surgery from September 2016 to September 2022. Results In patients subjected to cavity shaving, we reported a significant reduction in positive margins of 17.1% versus 28.7% (p-value = 0.042). Also, a difference in terms of surgical re-excision was reported as p-value = 0.039 (12.4% versus 23.8%, respectively, for the cavity shave and control group). In the multivariate analysis, intraoperative evaluation of the margins was a risk factor for margins re-excision (Wald = 4.315, p = 0.038, OR: 2.331 [95% CI: 1.049–5.180]). Surgical time was lower in patients subjected to cavity shaves (p = 0.024), and the relative mean time was 68.4 min ± 37.1 min in the cavity shave group versus 93.9 min ± 40.6 min in the control group. Conclusion The cavity shave margin technique in conserving breast surgery results in a reduction in positive margin rate, surgical re-excision, and operative time.